1993
DOI: 10.1104/pp.102.2.629
|View full text |Cite
|
Sign up to set email alerts
|

An in Vivo Nuclear Magnetic Resonance Investigation of Ion Transport in Maize (Zea mays) and Spartina anglica Roots during Exposure to High Salt Concentrations

Abstract: l h e response of maize (Zea mays 1.) and Spartina anglica root tips to exposure to sodium chloride concentrations in the range O to 500 mM was investigated using 23Na and "P nuclear magnetic resonance spectroscopy (NMR). Changes in the chemical shift of the pH-dependent 31P-NMR signals from the cytoplasmic and vacuolar orthophosphate pools were correlated with the uptake of sodium, and after allowing for a number of complicating factors we concluded that these chemical shift changes indicated the occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 27 publications
1
28
1
1
Order By: Relevance
“…Thus the response of C. intrepidus again emphasizes the effectiveness of the pH regulatory mechanisms in this species, and it could be argued that this might be a property of desiccation-tolerant and salt-tolerant plants. In support of this conclusion, pH cyt in the salt-tolerant grass Spartina anglica was much less affected by salt stress than maize root tips (Spickett et al, 1993), and similarly pH cyt was unaffected by PEG treatment in the desiccation-tolerant alga Prasiola crispa (Bock et al, 1996).…”
Section: supporting
confidence: 63%
See 4 more Smart Citations
“…Thus the response of C. intrepidus again emphasizes the effectiveness of the pH regulatory mechanisms in this species, and it could be argued that this might be a property of desiccation-tolerant and salt-tolerant plants. In support of this conclusion, pH cyt in the salt-tolerant grass Spartina anglica was much less affected by salt stress than maize root tips (Spickett et al, 1993), and similarly pH cyt was unaffected by PEG treatment in the desiccation-tolerant alga Prasiola crispa (Bock et al, 1996).…”
Section: supporting
confidence: 63%
“…These results contrast with those of Spickett et al (1992), who found that hyperosmotic shock caused a small alkalinization of both the cytoplasm and the vacuole in maize root tips. Suspending maize root tips in solutions with a water potential of k1n35 MPa caused an increase in pH cyt of between 0n05 and 0n1 pH units within 3 h of reducing the water potential of the suspending medium to k1n35 MPa with several non-ionic osmotica, and a similar effect was observed in response to salt stress (Spickett et al, 1993). The constancy of pH cyt in the submerged leaves of C. intrepidus during exposure to reduced water potential also contrasts with the cytoplasmic acidification of 0n2-0n3 pH units observed in leaf discs of Valerianella locusta incubated in hyperosmotic sorbitol (Daeter & Hartung, 1990).…”
Section: mentioning
confidence: 58%
See 3 more Smart Citations